Study of Shadow Banking in India with a Specific Reference to P2P-NBFCS - Sankar, Prudhvi; Bhattacharya, Mousumi (International Journal of Economics and Financial Issues, 2020)
The P2P lending is a form of crowd-lending and is regulated by RBI as NBFC-P2P. While the P2P lending existed in India from the beginning of this decade (2011-2020), RBI brought it under its ambit through its Master Directions of 2017. The regulations are definitely a good sign to augur the growth opportunities of P2P lending while inculcating a sense of trust and confidence in the participants of P2P lending. However, the regulations, in the process, have also limited the scope of P2P lending. This exploratory paper studies the P2P lending process in India, in general. This paper also studies the operating strategies and risk management strategies of the P2P companies registered with RBI as on April 30, 2019. Further, the financial statements of around ten P2P companies are analysed to understand the functioning of P2P companies in India. The study serves in recognising the future evolutionary aspects in today’s P2P lending framework. The study also points at few regulatory hurdles that needs to be tackled effectively in order to ensure that the potential gains of P2P lending is realised. Keywords: P2P, NBFC, Opportunities JEL Classifications: G23, G28 DOI: https://doi.org/10.32479/ijefi.10057